Resilience of Student Viewed from Gender, Culture Background and Attachment of parents and Implication in Guidance and Counseling - Vasco Delano; Daharnis Daharnis; Yeni Karneli (RedWhite Press, 2018)
Resilience by disaster need to be grown in individual’s self in order that does not become problem in the development of individual to become a better person. Many factors affect resilience, including gender, cultural background and attachment of parents. This study aims to test the relevancy of resilience with several factors. This research uses quantitative approach with comparative descriptive method. The population is 912 students with a sample amounts 278 students with using Proportional Random Sampling. The instrument used is Likert scale model. Data were analyzed by three way ANOVA technique. The results showed that gender and attachment of parents affect individual’s resilience while culture significantly has no relevance resilience. The implications of this research will be discussed.